Organic defaults in online-shopping: immediate effects but no spillover to similar choices - Kuhn, Sascha; Ihmels, Max; Kutzner, Florian (Journal of consumer behaviour, 2021)
Changing defaults—the preselection that becomes effective without active choice—is becoming a prominent policy tool, after having been proven to be effective in areas as varied as retirement savings, organ donation and product customization. Yet, little is known about how default effects spill over to subsequent similar behaviors. In an online shopping scenario, we found standard default effects on the share of organically produced products in the overall selection of products. These effects did not spill over to subsequent active shopping choices. This was true for defaults that were hard and easy to change (Exp. 1, N = 90), for immediate and delayed subsequent choices (Exp. 2, N = 106) and for self-selected defaults (Exp. 3, N = 181). These findings suggest that the reach and scalability of default manipulations in policy making may be limited, but also speak against the possibility for negative spillover.